The Effect of Practical Field Experience (PFE) on Interest in Becoming a Teacher of Islamic Education Department Students at a Private University in Yogyakarta, Indonesia - Wahyuni, Dinda (Universitas Muhammadiyah Yogyakarta, 2025)
Teachers play a crucial role in shaping the quality of the younger generation through their educational responsibilities, which include guiding, educating, training, teaching students, assessing, and evaluating across various educational levels. The quality of teachers greatly impacts the development of quality human resources, which is achieved by fulfilling four key competencies: pedagogical, personal, social, and professional, all of which are essential for teacher readiness. This study examines the effect of Practical Field Experience (PFE) readiness on the interest in becoming a teacher among students majoring in Islamic Education (IE). A causal quantitative approach was used in this research, employing a descriptive survey method with a population of 116 students and a sample of 89. The causal quantitative approach was used to explore the cause-and-effect relationships between variables. The research utilized nonprobability sampling with purposive sampling techniques, meaning the sample was not selected randomly. Data analysis involved descriptive statistics, normality tests, classical assumption tests, simple linear regression analysis, and the R-Square test. The findings indicate that readiness for PFE significantly influences students' interest in becoming teachers, as evidenced by data from IE Study Program students, with an R-Square value of 73.5%. However, other factors influencing this interest were not identified in this study.